Effectiveness Test of Ethanol Extract of Red Betel Leaves (Piper Crocatum Ruiz & Pav) Against Histopathological Features of The Pancreas and Blood Sugar Levels of Alloxan-Induced Male Mice (Mus Musculus L) - Sembiring, Mahral Effendi; Nasution, Ali Napiah; Chiuman, Linda (Jurnal EduHealth, 2023)
Diabetes Mellitus induces hyperglycemia. Low insulin production causes insulin resistance and altered protein, fat, and carbohydrate metabolism. Much research has shown that traditional herbal treatments can treat diabetes. Diabetes increases free radical production. Secondary metabolic plants include antioxidants that treat extreme illnesses like diabetes. This study examines the efficacy of ethanol extract from red betel leaves (EERBL) in lowering blood glucose levels in vivo, the optimal dose, secondary metabolite content based on phytochemical screening, and alloxan-induced pancreatic hyperglycemia histopathology. Mouse. Six 20-30 gram groups of mice were treated. Group III got 0.65 mg/kgBW glibenclamide, and Groups IV, V, and VI received oral gavage EERBL 100, 300, and 500 mg/kgBW. Group I was in standard control without alloxan, and Group II was in alloxan control. Hyperglycemic mice received 150 mg/kg BW intraperitoneal alloxan. Red betel is 96% ethanol-macerated. Oral red betel leaf extract was given for 21 days to monitor blood glucose and pancreatic function. Splitting red betel leaves to male mice significantly altered blood glucose and pancreatic histology. Red betel goes low cuts close and pancreatic histology by 58.4%. Blood glucose readings were Kruskal-Wallis significant at 0.004 or 0.05. Red betel leaf extract reduced blood glucose and enhanced pancreatic histology in male mice.